Alkali Metal Modification of Silica Gel-Based Stationary Phase in Gas Chromatography - Ashraf Yehia El-Naggar (Advances in Materials Science and Engineering)
Modification of the precipitated silica gel was done by treatment with alkali metal (NaCl) before and after calcination. The silica surfaces before and after modification were confirmed by infrared spectroscopy in order to observe the strength and abundance of the acidic surface OH group bands which play an important role in the adsorption properties of polar and nonpolar solutes. The surface-modified silica gels were tested as GC solid stationary phases in terms of the separation efficiency for various groups of non-polar and polar solutes. Also, thermodynamic parameters (ΔH, ΔG, and ΔS) were determined using n-hexane as a probe in order to show the adsorbate-adsorbent interaction. It was observed that the non-polar solutes could be separated Independent on the reactivity and porosity of the silica surfaces. The efficiency of the surface-modified silica gels to separate the aromatic hydrocarbons seemed to be strongly influenced by the density of the surface hydroxyls.